Dualcopter PID Controller - Tan, Mun Mun; Mohd Jamil, Muhammad Khairi Afiq; Mohamad Zapri, Muhamad Zarif Iman; Zahar, Mohd Muzaffar (Multidisciplinary Applied Research and Innovation, 2022)
A drone with 2 blades is known as dualcopter. This project is to build a stable dualcopter using PID controller in which it is only can move up and down without a remote control. Arduino UNO is the main components to create self-balancing of the dualcopter. Some practical studies on effect of derivative parameters on the settling time has been done to produce the best three values of PID. The testing of dualcopter to fly in equilibrium has been conducted and PID controller is suitable to be implemented for stabilizing the drone.